Beneficial effects and safety of traditional Chinese medicine for chronic inflammatory demyelinating polyradiculoneuropathy: A case report and literature review - Xie, Yao; Li, Lesang; Xie, Le; Jiang, Junlin; Yao, Ting; Mao, Guo; Wang, Shiliang; Lin, Anchao; Ge, Jinwen; Wu, Dahua (Frontiers in Neurology, 2023)
Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is an immune-mediated neuropathy. Corticosteroids, intravenous immunoglobulin, and plasma exchange are as first-line treatments for CIDP. However, the expensive costs, limited effectiveness, and adverse events always restrict the application. We explored a new potential effective and safety therapeutic to alleviate CIDP symptoms and improve the quality of life. In this case, a 47-year-old rural woman presented with progressive extremities weakness and numbness. According to the abnormal cerebrospinal fluid and electromyography, the patient was diagnosed as CIDP. This patient was treated with 1-week intravenous dexamethasone and Huangqi-Guizhi-Wuwu & Bu-Yang-Huan-Wu decoction for 90 days. Surprisingly, the weakness and numbness were eliminated, and quality of life was also improved. The treatment effects were also reflected in the varied scores of INCAT, MRC, BI. During the follow-up, the symptoms did not relapsed after 8 months discharge. We also screened PubMed, EMBASE, Web of Science, Cochrane library, Chinese National Knowledge Infrastructure Databases, Wanfang, and Chongqing Chinese Science and Technology Periodical Database for “traditional Chinese medicine (TCM)” and “CIDP”. Finally, only 10 studies were included in literature review. Among those, 3 studies were randomized controlled trails, and 7 studies were case report or case series. A total of 419 CIDP patients were involved, but all study sites were in China. Nine TCM formulas involving 44 herbs were reported, and huangqi (Astragalus Membranaceus) was the most core herb. In conclusion, the case and literatures showed TCM treatment may be a better effective, low cost, and safety option for CIDP. Although these preliminary results are promising, further studies with larger sample size and higher quality randomized clinical trials are urgently needed to confirm our findings.